STRATEGI PENGENALAN BAHASA INGGRIS PADA ANAK USIA DINI DI TK SANTA MARIA BANJARMASIN - Nor Izzatil Hasanah; Nadiya Ulya (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2020)
This research discusses about the strategy of introducing English in the TK Santa Maria Banjarmasin, include in this research is: methods, media, materials and assessment . This research is descriptive qualitative, the subject of this research are 12 children from class A1 and 13 children from A2 and 1 English teacher in Santa Maria Banjarmasin. The data collected by using of observation, interviews, and documentation. The data analysis in this research used Milles and Huberman which was conducted interactively using data consisting of reductions, presenting data, and conclusion(coding). The results of research shoved every English teaching in TK Santa Maria Banjarmasin that appropriate in the learning process in accordance with the child's development, English development strategies that are equipped: 1) Learning methods used when carrying out activities introducing English methods such as singing , game , listen and repeat, questions and answer and make matches. 2) The media used are display media and worksheets. 3) The material introduces English to children in this school are family, animals, healthy food and Christmas. 4) The assessment used are observation, children product, conversation and anecdotes.